Caffeine use in sports: Considerations for the athlete - Sokmen, B.; Armstrong, L. E.; Kraemer, W. J.; Casa, D. J.; Dias, J. C.; Judelson, D. A.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2008)
The ergogenic effects of caffeine on athletic performance have been shown in many studies, and its broad range of metabolic, hormonal, and physiologic effects has been recorded, as this review of the literature shows. However, few caffeine studies have been published to include cognitive and physiologic considerations for the athlete. The following practical recommendations consider the global effects of caffeine on the body: Lower doses can be as effective as higher doses during exercise performance without any negative coincidence; after a period of cessation, restarting caffeine intake at a low amount before performance can provide the same ergogenic effects as acute intake; caffeine can be taken gradually at low doses to avoid tolerance during the course of 3 or 4 days, just before intense training to sustain exercise intensity; and caffeine can improve cognitive aspects of performance, such as concentration, when an athlete has not slept well. Athletes and coaches also must consider how a person's body size, age, gender, previous use, level of tolerance, and the dose itself all influence the ergogenic effects of caffeine on sports performance.